CITRAAN GERAK PADA KUMPULAN SAJAK LUPUT KARYA IDRUS TINTIN - Mohd.Adhli '; Syafrial '; Elmustian ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: Through research and discussion that has been done can be formulated conclusion that the motion images at set Sajak Escape K. Tintin works used by the author in a poem entitled